1985
DOI: 10.1136/bmj.291.6495.604-b
|View full text |Cite
|
Sign up to set email alerts
|

Failure to detect eye muscle membrane specific autoantibodies in Graves' ophthalmopathy.

Abstract: and successful treatment cannot always be guaranteed.We would therefore suggest that patients who have radical chemotherapy for P vivax should be warned of the possibility of relapse up to two years after leaving an endemic area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Circulating autoantibodies directed against various retroocular tissue preparations (sometimes called ophthalmic Igs) have been described previously (8)(9)(10)(11) indentifiable cellular population in the ocular tissue preparations and cross-react with antigens from other tissues (11). One report of human eye muscle membranespecific antibodies in serum of patients with active severe GO (10) has been questioned by other investigators (18). The possible existence of circulating antibodies to skin fibroblasts was shown by the isolation of a monoclonal antibody to the TSH receptor from the peripheral lymphocytes of a patient with GO (19) which stimulated collagen synthesis by skin fibroblasts.…”
Section: Discussionmentioning
confidence: 96%
“…Circulating autoantibodies directed against various retroocular tissue preparations (sometimes called ophthalmic Igs) have been described previously (8)(9)(10)(11) indentifiable cellular population in the ocular tissue preparations and cross-react with antigens from other tissues (11). One report of human eye muscle membranespecific antibodies in serum of patients with active severe GO (10) has been questioned by other investigators (18). The possible existence of circulating antibodies to skin fibroblasts was shown by the isolation of a monoclonal antibody to the TSH receptor from the peripheral lymphocytes of a patient with GO (19) which stimulated collagen synthesis by skin fibroblasts.…”
Section: Discussionmentioning
confidence: 96%
“…Many investigators have searched for and found, antibodies to extraocular muscle cell membranes in patients with Graves' ophthalmopathy. The pathogenic potential of anti extraocular muscle antibodies was demonstrated by Wang et al [13] and Hiromatsu et al [14] but they did not Graves' ophthalmopathy 27 report testing their antibody in an ELISA or a RIA with a membrane preparation.…”
Section: Antibodies To Extraocular Muscle Antigensmentioning
confidence: 99%
“…Other authors [5,6,8,9,10,12] resorted to the use of extraocular muscles of non-human origin to avoid aspecific binding of anti-human immunoglobulin antibodies. Sikorska et al [27,28] demonstrated that a human eye muscle membrane preparation reacted with an anti-human Ig antiserum.…”
Section: Specificity Of the Antibodies To Extraocular Muscle Antigensmentioning
confidence: 99%
“…The methods used have been enzyme-linked immunosorbent assay (Kodama et al, 1982;Kendall-Taylor et al, 1984;Ahmann et al, 1987), staphylococcal protein A binding procedure (Faryna et al 1985), or immunofluorescence technique (Mengistu et al, 1986). However, difficulties in reproducing some of these findings have been reported (Sikorska & Wall, 1985;Wall & Kuroki, 1985).…”
mentioning
confidence: 99%